1990
DOI: 10.1016/0735-1097(90)90180-w
|View full text |Cite
|
Sign up to set email alerts
|

Apical hypertrophic cardiomyopathy: Clinical follow-up and diagnostic correlates

Abstract: To determine the clinical course of apical hypertrophic cardiomyopathy, 26 patients (mean age 45 years) with asymmetric apical hypertrophy diagnosed by echocardiography or angiography were followed up for an average of 7.3 years (range 1 to 22). Presenting symptoms included atypical chest pain (n = 10), typical angina (n = 6), dyspnea (n = 5) and palpitation (n = 8). Ten patients were asymptomatic. At follow-up all patients had inverted precordial T waves, and 14 had the syndrome of "giant T wave negativity" (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
1
14

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 23 publications
5
84
1
14
Order By: Relevance
“…Webb et al reported loss of precordial giant T-wave negativity with formation of an apical aneurysm during a 17-year follow-up in a patient with apical hypertrophy and normal coronary arteries. 9 Although the electrocardiogram of the present case was similar to the one that Webb et al reported (Fig 1), it only suggests the complication of apical myocardial aneurysm with left ventricular hypertrophy after loss of giant T-wave negativity.…”
Section: Discussionsupporting
confidence: 80%
“…Webb et al reported loss of precordial giant T-wave negativity with formation of an apical aneurysm during a 17-year follow-up in a patient with apical hypertrophy and normal coronary arteries. 9 Although the electrocardiogram of the present case was similar to the one that Webb et al reported (Fig 1), it only suggests the complication of apical myocardial aneurysm with left ventricular hypertrophy after loss of giant T-wave negativity.…”
Section: Discussionsupporting
confidence: 80%
“…Poucos são os relatos de casos da forma apical, que evoluíram com infarto agudo do miocárdio (IAM), sem 8,9 ou com aterosclerose associada [10][11][12] . O encontro de angina do peito é comum nos pacientes mais idosos com este tipo de agressão 11 .…”
Section: Discussionunclassified
“…Esta série era composta por pacientes com maior faixa etária (62±11 anos) 11 . Na sé-rie de Webb e col 8 em Toronto, dos 26 pacientes com CMHA, apenas um apresentou aos 33 anos infarto do miocárdio apical e formação de aneurisma, estava em seguimento ambulatorial desde os 17 anos, tendo ocorrido o desaparecimento das alterações da onda T e surgido elevação persistente de supra desnível do segmento ST-T entre V 3 -V 6 . O estudo coronariográfico não evidenciou nenhuma alteração obstrutiva das artérias coronárias, posteriormente desenvolveu arritmia ventricular letal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This variant of HCM is characterized by giant T wave inversion and an angiographic 'ace-of-spades'-shaped appearance of the left ventricle. In subsequent studies from centers outside Japan, [19][20][21][22][23][24] most of the non-Japanese patients with the apical form of HCM did not have the characteristic giant negative T waves. The reason for the different phenotypic expression of apical hypertrophy in different parts of the world is unknown, but it is most likely related to differences in patient selection.…”
Section: Discussionmentioning
confidence: 99%